Radical Chemoradiotherapy for Urethral Squamous Cell Carcinoma: Two Case Reports and a Review of the Literature - H. Coop; L. Pettit; C. Boon; P. Ramachandra (Case Reports in Urology)
Primary urethral squamous cell carcinoma is rare. Its management is particularly challenging owing to the paucity of evidence from randomised trials to inform practice. We report two male and female cases of squamous cell carcinoma of the urethra, which were treated with concomitant cisplatin and radiotherapy. These cases add to the body of case reports that have shown benefit for concomitant chemoradiotherapy in urethral squamous cell carcinoma. They also illustrate that single agent chemotherapy, namely, cisplatin, may be used successfully with limited toxicities.